Antithyroglobulin Antibody Variation During Follow-Up Has a Good Prognostic Value for Preoperative Antithyroglobulin Antibody-Positive Differentiated Thyroid Cancer Patients: A Retrospective Study in Southwest China - Liu, Qianhui; Yin, Mengting; Li, Guixing (Frontiers in Endocrinology, 2021)
Objective: Antithyroglobulin antibody (TgAb) is a potential tumor marker for the detection of recurrence of DTC, but there are not sufficient data supporting its application in clinical work. Our study aimed at describing change trend of TgAb after surgery and finding the relationship between this trend and clinical outcomes. Patients and methods: We reviewed electronic records of 1686 DTC patients who had undergone total thyroidectomy (TT) and radioactive iodine (131I) therapy in West China hospital of Sichuan University from January 2015 to December 2017. Finally, 393 preoperative TgAb-positive DTC patients were included and divided into 4 subgroups depending on clinical outcomes: Group A (Tumor Free), Group B (Uncertain), Group C (Incomplete Biochemical Response) and Group D (Structural Disease). Patient demographics, tumor characteristics, operation, pathology reports and all serological biomarkers were reviewed and compared, and the prognostic efficacy of TgAb was evaluated. Results: In all 1686 patients, 393 patients (23.65%) had preoperative TgAb positive (>40 IU/mL). TgAb in Group A dropped significantly after surgery and 131I therapy, and tended to stabilize at the low level after 1-2 years of 131I therapy. But in other three groups, the drops of TgAb were not significant after treatment, and conversely TgAb declined slowly, kept stable or rising. The variations of TgAb relative to preoperative level of Group A were significantly bigger than Group B, C, D at most time points of follow-up (P<0.001). By ROC analyses, the variations of TgAb <-77.9% 6 months after 131I therapy (AUC=0.862, P<0.001) and <-88.6% two years after 131I therapy (AUC=0.901, P<0.001) had good prognostic efficacy on tumor free. When the variation of TgAb ≤-88.6% at 2 years after 131I therapy was incorporated as variables in the ATA categories, both intermediate- and high-risk patients also had a significantly increased chance of having tumor free (from 75.68% to 93.88%, and 42.0% to 82.61% respectively). Conclusions: For preoperative TgAb-positive DTC patients, the variations of TgAb <-77.9% 6 months after 131I therapy and <-88.6% two years after 131I therapy had good prognostic efficacy Their incorporations as the variables in the ATA risk stratification system could more accurately predict disease free.